SISTEM PENGAMANAN MOBIL BERBASIS PLC MENGGUNAKAN IP CAMERA - Muslim, Ahmad Saeful; Prasetia, Ditya; Taufik, Ridwan (Program Kreativitas Mahasiswa - Karsa Cipta, 2013)
Monitoring technology is growing at this time can be used to reduce motor vehicle theft especially in the car. This is done, because of the lack of existing security systems in motor vehicles. For that, they invented a tool that can reduce theft, is to create a tool that auto security system controlled by PLC with the IP Camera, which can send an early warning to the owner of the car by SMS and send proof IP Camera catches image via email. Monitoring using the Internet IP Camera using media that can be accessed remotely. PLC will shut off the car so the owner can immediately come to the site, so avoid car theft. This tool can send you early notification via SMS with 90% success rate close to BTS (quiet hours) and 70% near the BTS (rush hour), 80% away from the BTS (quiet hours) and 60% away from the BTS (rush hour). Tool thief can send pictures via email proof with 96.67% success rate close to BTS (quiet hours) and 83.33% close to BTS (rush hour), 90% away from the BTS (quiet hours) and 80% away from the BTS (hours busy).